KADAR C-REACTIVE PROTEIN, D-DIMER, DAN LAKTAT DEHIDROGENASE SEBAGAI PREDIKTOR LUARAN COVID-19 PADA ANAK: SEBUAH KAJIAN SISTEMATIS: sebuah kajian sistematis - Macmilliac Lam; Laureen Celcilia (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Coronavirus Disease (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). During a surge in COVID-19 cases, Indonesia has the highest child mortality rate due to COVID-19. Until now, there have not been many studies that explain the laboratory characteristics of COVID-19 in children. This systematic review aimed to assess the significance of laboratory findings, specifically c-reactive protein (CRP), D-dimer, and lactate dehydrogenase (LDH), to predict the severity of COVID-19 in children. Methods: A systematic review was conducted through PubMed, Scopus, Cochrane, and Google Scholars to search for studies analyzing the prognostic value of c-reactive protein (CRP), D-dimer, and lactate dehydrogenase (LDH) in children with COVID-19. Quality assessments of studies were performed using the Newcastle-Ottawa Scale. Discussion: The search yielded 11 studies with a total of 3424 subjects. C-reactive protein (CRP) levels were significantly increased in pediatric patients with severe/critical COVID-19. The concentration of CRP can reflect the severity of the disease and the magnitude of the acute inflammatory response. Moreover, children with complications had higher levels of c-reactive protein (CRP) and D-dimer. Conclusion: In conclusion, c-reactive protein (CRP) levels can be a potential biomarker to improve early identification and treatment of severe COVID-19 disease in children. Further studies on D-dimer and lactate dehydrogenase (LDH) levels as markers of COVID-19 severity are still needed to provide strong recommendations.